1990
DOI: 10.1177/019459989010300620
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole in head and neck surgery—The effect of lengthened prophylaxis

Abstract: Previous studies of antibiotic prophylaxis have shown that treatment for 24 hours has been beneficial for head and neck surgery and that longer periods of antibiotic therapy have not improved results. Metronidazole (Flagyl), unlike other antibiotics tested, has been shown to be effective in an experimental abscess, even if treatment is begun up to 120 hours after administration of inoculum. This article presents a prospective, randomized, multifactorial study comparing a brief vs. a prolonged duration of metro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 7 publications
(3 reference statements)
0
8
0
Order By: Relevance
“…Carroll et al [47] confirmed this for clindamycin in patients undergoing free flap reconstruction, finding no difference in the SSI rate between 1 or 5 days of ABP (p = 0.99). These data suggest no beneficial effect from an antibiotic course for longer than 24 h. Contrary to this finding, Sawyer et al [45] compared 2 days of administration of cefazolin-metronidazole to more than 7 days in patients undergoing free flap reconstruction and found less cases of wound infection in the long-term group (p = 0.04). This conclusion is again in contrast to a more recent review in which the authors found no difference in efficacy between administration of antibiotics for less or more than 2 days (p = 0.74), but a higher risk of pneumonia in patients undergoing long course antibiotic regimens (p = 0.03) [34].…”
Section: Prolonged Antibiotic Course In Patients Undergoing Flap Recomentioning
confidence: 90%
“…Carroll et al [47] confirmed this for clindamycin in patients undergoing free flap reconstruction, finding no difference in the SSI rate between 1 or 5 days of ABP (p = 0.99). These data suggest no beneficial effect from an antibiotic course for longer than 24 h. Contrary to this finding, Sawyer et al [45] compared 2 days of administration of cefazolin-metronidazole to more than 7 days in patients undergoing free flap reconstruction and found less cases of wound infection in the long-term group (p = 0.04). This conclusion is again in contrast to a more recent review in which the authors found no difference in efficacy between administration of antibiotics for less or more than 2 days (p = 0.74), but a higher risk of pneumonia in patients undergoing long course antibiotic regimens (p = 0.03) [34].…”
Section: Prolonged Antibiotic Course In Patients Undergoing Flap Recomentioning
confidence: 90%
“…182 In an RCT using metronidazole and cefazolin, lower infection rates were seen with a 7-day compared to a 2-day postoperative antibiotic course (28% vs 20%, P \ .05). 183 Multiple additional studies consistently show that duration of antibiotics for greater than 24 hours and the use of extended preoperative antibiotic use have no added benefit. 139,140,[143][144][145]148,159,[184][185][186][187][188][189][190][191][192][193][194] Microvascular free flaps are a unique entity within cleancontaminated surgery.…”
Section: Clean Head and Neck Surgery Recommendationmentioning
confidence: 99%
“…Our overall wound complication rate of 28.1 per cent is comparable to results reported previously for chemoprophylaxis in head and neck oncological surgery, but greater than the 20 per cent rate reported by Sawyer et al for the initial 25 patients studied using this seven-day regimen. (Sawyer et al, 1990). Saginur reported a 33 per cent incidence of wound complications with Mandol, while Mandell-Brown reported an identical rate for cephazolin alone.…”
Section: Discussionmentioning
confidence: 99%
“…Various prophylactic antibiotic regimens for major head and neck oncological procedures have been investigated, and many differing conclusions have been reached regarding optimal choice and duration of chemotherapeutic prophylaxis. (Becker and Parell, 1979;Goode et al, 1979;Becker, 1981;Suarez et al, 1981;Brand et al, 1982;Fee et al, 1984;Panosetti et al, 1987;Johnson and Yu, 1988;Robbins et al, 1988;Saginur et al, 1988;Friberg and Lundberg, 1990;Sawyer et al, 1990). In all cases, the use of prophylactic antibiotic therapy has been shown to reduce the incidence of postoperative infection related wound complications, and has become the standard of care in cleancontaminated head and neck surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation